2010
DOI: 10.1080/17458080903115387
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of silver nanoparticles into dendritic flowers from aqueous solution

Abstract: Similar to folding of proteins into three-dimensional (3D) structure, self-assembly of metallic nanoparticles (NPs) into dendritic or other supramolecular structures is of greater interest, yet less understood. We observed spontaneous, template-free organisation of silver NPs into 3D, dendritic, elegant, flower-like structures from an aqueous solution containing AgNO 3 and L-cysteine (Cys). The resultant NPs and dendritic structures were characterised using UV-Vis spectroscopy and scanning and transmission ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…It is also revealed that the intensity of the wide absorption band increases due to the formation of a large number of highly dense nanoparticles most likely by diffusion-limited-aggregation (DLA). 23 As reported before, 24 the wide absorption over the near infra red region of the absorption spectrum is due to red shift of relatively intense in-plane dipole resonance where the size distribution and high degree of alignment of the dendritic structure is present.…”
Section: Results and Analysismentioning
confidence: 63%
“…It is also revealed that the intensity of the wide absorption band increases due to the formation of a large number of highly dense nanoparticles most likely by diffusion-limited-aggregation (DLA). 23 As reported before, 24 the wide absorption over the near infra red region of the absorption spectrum is due to red shift of relatively intense in-plane dipole resonance where the size distribution and high degree of alignment of the dendritic structure is present.…”
Section: Results and Analysismentioning
confidence: 63%
“…Absorptions peaks centered between 270 and 300 nm are in place of those related to nanoparticles and can be assigned to different clusters of silver ions such as Ag + , Ag +2 , Ag +3 [33][34][35]. This means that the majority of Ag + ions chemically interact with the dilute acetic acid and form CS/silver acetate as a source of silver ions [27].…”
Section: Uv-vis Spectroscopy Analysismentioning
confidence: 97%
“…This reaction can be written as Such a reaction scheme was proposed in ref. 37 in the study of the creation of silver nano-particles forming fractal dendritic flowerlike structures. The authors of the cited publication used the same reagents as in this study but taken in other ratios and concentrations.…”
Section: About Component Interaction and The Structure Of The Networkmentioning
confidence: 99%